Produção de videotutoriais como apoio à gestão do portal de projetos SIE - web da UFSM - Menin, Lovaina Aparecida Batista Ribeiro (2019)
This dissertation was developed in the Graduate Program in Networked Educational Technologies (PPGTER) of the Federal University of Santa Maria (UFSM), in the Area of Concentration of Networked Educational Technologies for Innovation and Democratization of Education, in the research line Management. of Networked Educational Technologies. Its main objective was to produce instructional material to facilitate the use of the Project Portal / SIE-Web, with a view to guiding the workflow of teachers and administrative technicians of the Federal University of Santa Maria making the system a more efficient management tool. Specifically, we sought to: a) evaluate the Project Portal, as well as its current tutorial; b) map the routines, processes and workflows that involve the management of the Portal; c) identify weaknesses in relation to the various stages of use of the system and propose improvements based on the data collected. This is a descriptive case study with characteristics of documentary research and data analysis with a qualitative approach. Participating observation, field diary, questionnaires and semi-structured interviews were used as data collection instruments. The results of the study showed that the Project Portal presents some usability issues when performing specific tasks in its context of use, but it is a much better system than previously used and that like any other system needs to be constantly improved so that follow the needs of the institution and also the user. It was observed that the tutorial that accompanies the Portal is an important tool, but some are unaware of it and others due to the large number of pages do not have the habit of consulting it. It is believed that the video tutorials produced will help the user to maintain their projects registered in the Portal, as they were well received by the coordinators in the testing phase, which verified performance (efficiency and effectiveness) in the resolution of issues. . In addition to the benefits to users, it is expected that the developed tool will contribute to the activities and routines of UFSM Project Offices.